Psychotherapy in the Perspectives of Carl Jung and Ibn Qayyim: A Conceptual Comparison of the Soul and Healing Approaches - Faza Islami; Jarman Arroisi (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2025)
Modern life has been accompanied by forms of psychological distress that religiously grounded frameworks and secular psychology describe in different vocabularies. This study addresses a conceptual gap: comparative discussions of Carl Gustav Jung and Ibn Qayyim al-Jawziyyah often present the two thinkers asymmetrically and understate Jung's own engagement with religion. The purpose of this article is to compare, on textual grounds, how each thinker conceptualises the soul and the aims and means of psychological healing. The study uses a qualitative library method structured as a comparative conceptual and textual analysis, examining primary works by Jung and by Ibn Qayyim across five predefined dimensions: the anthropology of the person, the source of suffering, the goal of therapy, the primary resources of healing, and the status accorded to religion. The analysis finds the two frameworks to be partly commensurable and partly incommensurable: both treat the interior life as central to well-being and both give religious symbolism a serious role, yet they differ in the ontological status they assign to the soul and in whether religion functions as psychological symbol (Jung) or as revelatory and normative source (Ibn Qayyim). The study's contribution is a balanced conceptual map rather than a claim of clinical superiority; because the comparison is textual, it makes no assertion about comparative treatment outcomes. The findings suggest that Ibn Qayyim's psycho-spiritual anthropology offers distinctive conceptual resources for dialogue with analytical psychology, while both frameworks are best integrated with, rather than substituted for, professional mental-health care.